Bandidaje y épica: Los orígenes históricos del «Cantar de Sandailia» - Fernández de Larrea Rojas, Jon Andoni (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2008)
One of the few fragments that have been conserved from the Basque medieval epic is the Cantar de Sandailia. Documents in the Municipal Archives in Mondragón confirm the historicity of the events it narrates and to date these events precisely to the autumn and winter of 1457 and 1458.